ANALYSIS OF THE INCIDENCE OF STUNTING IN CHILDREN UNDER FIVE - Widya Nuriska; Akhmad Dwi Priyatno; Ali Harokan (LPPM STIKES Al-Ma'arif Baturaja, 2024)
Stunting is a condition of growth failure in toddlers which is characterized by a height-for-age figure of less than -2 (z-score value). The prevalence of stunting in children aged 6-59 months is 41.1%, factors related to stunting are the child's age, food source and children with stunting are more susceptible to disease. This study aims to determine factors related to the incidence of stunting in children under five in the Tanjung Batu Community Health Center UPT Working Area, Ogan Ilir Regency in 2024. The design of this research is quantitative with a cross-sectional approach. The population of this study is the target number of children under five who will be served/weighed at the Tanjung Batu Community Health Center, Ogan Ilir Regency in 2024. The sample in this study was 96 people. The sample collection method used purposive sampling with the inclusion criteria of children under five in the Puskesmas working area and bringing a KIA book. This research was carried out on March 1-30 2024. Data was collected using a questionnaire. Bivariate data analysis used the Chi-Square test and multivariate logistic regression. The results of the research show that there is a relationship between age (p value 0.003), nutritional status (p value 0.020), body weight (p value 0.009) and knowledge (p value 0.018) on the incidence of stunting in children under five in the working area of ​​the UPT Puskesmas Tanjung Batu, Ogan Ilir Regency In 2024. There is no relationship between exclusive breastfeeding (p value 0.11) and comorbidities (p value 0.20) on the incidence of stunting in children under five in the working area of ​​the UPT Puskesmas Tanjung Batu, Ogan Ilir Regency in 2024. The most dominant factor with The incidence of stunting in children under five in the working area of ​​the UPT Puskesmas Tanjung Batu, Ogan Ilir Regency in 2024 is knowledge (p value 0.012) OR (0.318). The community health center can increase public knowledge by providing health education about stunting through classes for mothers of toddlers, social media, leaflets and posters.